Effects of crowding and intermittent feed intake on growth performance and development of stomach lesions in finishing pigs - P Sorrell; L L Burnham; I H Kim; G A Kennedy; Robert H Hines; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1995)
Pigs in uncrowded pens (12 ft^2/pig) consumed more feed, gained at a greater rate, and tended to develop fewer stomach lesions than pigs in crowded pens (6 ft^2/pig). Pigs with ad libitum access to feed consumed more feed and gained at a greater rate than pigs deprived of feed for 24-h periods twice each week. The resulting intermittent feed intake increased the severity of stomach lesions but only for uncrowded pigs. In conclusion, crowding slowed growth for all pigs and increased the severity of stomach lesions. Intermittent feed intake also slowed growth, but its effects on development of stomach lesions were less consistent.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Finishing; Ulcers; Crowding; Feeding pattern